2021
DOI: 10.1097/icb.0000000000000788
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography Imaging of a Congenital Simple Hamartoma of the Retinal Pigment Epithelium

Abstract: To report the case of a small pigmented tumor in the macular region investigated using optical coherence tomography angiography (OCT-A) in the context of a multimodal approach.Methods: Case report Results: A 24-year-old man was referred for evaluation of an asymptomatic unilateral round comma-shaped pigmented tumor located in the macular region of his right eye. Spectral-domain OCT revealed an irregular hyperreflective mass within the retina, with a thickened hyaloid membrane and abrupt margins, and a complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In agreement to Gass [3] description of intrinsic vasculature as an element to characterize CSHRPE, the present report also demonstrated an exclusive vascular circuit distinguishing from other OCTA reports [6, 7], as well as an evident patent feeder vessel (Figs. 2, 3) as published by Shields and colleagues [1] in 100% of their cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement to Gass [3] description of intrinsic vasculature as an element to characterize CSHRPE, the present report also demonstrated an exclusive vascular circuit distinguishing from other OCTA reports [6, 7], as well as an evident patent feeder vessel (Figs. 2, 3) as published by Shields and colleagues [1] in 100% of their cases.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Arjmand et al [6] and Zola et al [7] reported a case imaged with optical coherence tomography angiography (OCT-A) for noninvasive assessment of the intrinsic retinal microvasculature. Similar to them, we explored OCT-A of this mass and found better microvasculature detail than with fluorescein angiography (FA).…”
Section: Introductionmentioning
confidence: 99%
“…3 Several studies have described hypoautofluorescence of the lesions on FAF images and hypofluorescence in early-phase fluorescein angiography (FA) with/ without discrete hyperfluorescence around the lesion in the late phase of the angiogram. 3,[5][6][7] Fluorescein angiography may reveal feeder vessels related to the lesion. Similar to other studies, [5][6][7][8][9] the current case had intrinsic flow to the pigmented lesions at the SCP, seen bilaterally on OCTA and more evident in the left eye (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescein angiogram shows hypofluorescence of the black lesion and hyperfluorescence at the depigmentation within the lesion [ 7 ] or at the margin with or without a hyperfluorescent halo [ 7 ]. Depigmentation within the lesion may correspond to the intrinsic vasculature of the hamartoma [ 8 ].…”
Section: Discussionmentioning
confidence: 99%